Design guidelines for scaffolding pre‐service teachers' reflection‐in‐action toward culturally responsive teaching. Issue 5 (2nd September 2020) - Umutlu, Duygu; Kim, ChanMin
ABSTRACT: Pre-service teachers need to prepare for diverse classrooms. Being culturally responsive, they should affirm students from diverse cultures and acknowledge that both their own and these students' cultural practices may shape learning in classrooms. Yet, many teacher education programs often fall behind in terms of focusing on cultural elements. One way to prepare pre-service teachers for culturally responsive teaching is integrating critical reflection into teacher education curricula. Pre-service teachers' reflections tend to be descriptive rather than in-depth. Also, usually, retrospective reflection is practiced in teacher education programs, but pre-service teachers should also learn reflection- in -action, reflection in the moment of an action, for effective teaching in dynamic atmosphere of classrooms. This paper offers a set of literature-driven guidelines for future teachers' learning of culturally responsive teaching through critical reflection- in -action. The conceptual design guidelines presented in this paper focus on how digital scaffolds can be designed to promote pre-service teachers' reflection-in-action in their future diverse classrooms.